THE STRATEGIES IN TRANSLATING SWEARING WORDS IN MARK MANSON’S THE SUBTLE ART OF NOT GIVING A FUCK INTO INDONESIAN SEBUAH SENI UNTUK BERSIKAP BODO AMAT BY F. WICAKSONO - Sinaga, Feby Yurista (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2022)
This paper investigates swearing words in Mark Manson’s The Subtle Art of Not Giving a Fuck as translated into “Sebuah Seni Untuk Bersikap Bodo Amat” by F. Wicaksono. This paper aims to identify the translation strategies and subsequently classify them into understandable patterns. Using a qualitative approach, this study finds five strategies used in translating swearing words: paraphrasing, general words, omission, cultural substitution, and neutral words. Moreover, eight types of swearing words are also found: idiomatic set phrase, emphatic intensifier, general expletive, predicative negative adjective, cursing expletive, literal usage, pronomial form, and destinational usage. The translator mostly used paraphrasing strategies.